2011
DOI: 10.1016/j.neuroimage.2010.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Species sensitivity of early face and eye processing

Abstract: Humans are better at recognizing human faces than faces of other species. However, it is unclear whether this species sensitivity can be seen at early perceptual stages of face processing and whether it involves species sensitivity for important facial features like the eyes. These questions were addressed by comparing the modulations of the N170 ERP component to faces, eyes and eyeless faces of humans, apes, cats and dogs, presented upright and inverted. Although all faces and isolated eyes yielded larger res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
67
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 38 publications
18
67
2
Order By: Relevance
“…Eye sensitivity was previously demonstrated by a larger N170 for isolated eyes than whole faces (Bentin et al, 1996;Itier et al, 2006;Itier et al, 2007;Itier et al, 2011;Kloth et al, 2013;Taylor et al, 2001a,b). For this reason Bentin et al (1996) initially suggested that the N170 might reflect the activity of an eye detector.…”
Section: In Support Of the Eye Detector Hypothesismentioning
confidence: 89%
See 4 more Smart Citations
“…Eye sensitivity was previously demonstrated by a larger N170 for isolated eyes than whole faces (Bentin et al, 1996;Itier et al, 2006;Itier et al, 2007;Itier et al, 2011;Kloth et al, 2013;Taylor et al, 2001a,b). For this reason Bentin et al (1996) initially suggested that the N170 might reflect the activity of an eye detector.…”
Section: In Support Of the Eye Detector Hypothesismentioning
confidence: 89%
“…This featural sensitivity does not include other facial features as nose and mouth elicit delayed and smaller N170s than faces (Bentin et al, 1996;Nemrodov & Itier, 2011;Taylor et al, 2001b). However, eyeless faces elicit N170s with amplitudes similar to normal intact faces, albeit delayed (Eimer, 1998;Itier et al, 2007;Itier et al, 2011;Kloth et al, 2013) and this finding has been interpreted as supporting the view that the N170 reflects a holistic processing stage rather than an eye detector.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations